Kontribusi Bank Sampah Berbasis Digital sebagai Alternatif Peningkatan Pendapatan Warga - Kodriyah Kodriyah; Denny Kurnia; Agni Ambya Alamsyah; Agatha Rossy Wulandari (Penerbit Goodwood, 2022)
Purpose: The service team aims to provides alternative solutions to overcome waste management problems, namely by providing assistance to residents through outreach activities and education to residents about waste management that is considered useless to have economic value, formation of waste bank agents, registration assistance to weighing assistance. Methodology: The implementation of this community service starts from analyzing the problem, then conducting education and socialization as well as providing assistance in the formation of a Waste Bank. Results: The result of this service activity are the formation of the Bank Sampah Hijau Bina Mandiri and its management, and the registration of the Bank Sampah to Main office Bank Sampah Digital a total of 52 members with selected types of saving being money savings, basic necessities saving, sacrificial saving, umroh saving. Weighing of waste is carried out in the second month of this activity with a total of 208 kilograms of waste according to is type with a total income of IDR 384.900. this amount is certainly an additional income for residents from waste management Conclusion: This activity has a positive impact, namely residents have awareness, knowledge and understanding of the impacts arising from improper waste management, and encourage active participation of residents to protect the environment by converting waste that is considered useless into having economic value so that there is an increase in residents' income.